LEARNING MADE EASY WITH SCIENTIFIC MEMORY TECHNIQUES AND BRAIN SCIENCE (CAHIERS MAGELLANES-NS, 2024)
The twenty-first century is considered to be the era of globalization, telecommunication and digital technology. These advancements in science, information and technology have proved to be a boon in many fields (for example – electronic gadgets like mobile phones, computers etc.) and have also helped in the complexities of life (for example – internet addiction, mobile phone addiction etc.). Have also contributed.These complexities demand solutions to pre-existing problems as well as new problems in different areas. Many of these problems are important because they relate to the survival of mankind. This is where the role of creativity becomes relevant as it helps in providing unique solutions to problems. Memory in the brain is a mutual combination of any two information, this is what we call association.If we use this association as a method, then we can remember everything that we want to remember. The importance of remembering anything is only when it is remembered on time. To remember whatever is in your mind in the form of memory, what we do is ask any information related to it in the form of a question.